1981
DOI: 10.3758/bf03212030
|View full text |Cite
|
Sign up to set email alerts
|

Neophobias and conditioned taste aversions in rats following exposure to novel flavors

Abstract: Rats were successively exposed to three solutions with distinctively different flavors and then tested for both neophobia and propensity to form conditioned taste aversions to a fourth distinctively flavored solution. All permutations between the four solutions (salty, bitter, sweet, and sour) were examined. The prior exposures resulted in attenuation of neophobia to novel salty and sour solutions, but not to equally novel bitter or sweet solutions.. These effects were found to depend upon the diversity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
2

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 32 publications
3
7
2
Order By: Relevance
“…These results support the view that novelty may reflect a general process that is not necessarily related to the flavor-specific properties (e.g., taste or intensity) of the stimuli used (Miller & Holzman, 1981). The nonspecific character of novelty conceivably may have permitted the influence of novel flavor preexposure to endure the acquisition ofCTA.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results support the view that novelty may reflect a general process that is not necessarily related to the flavor-specific properties (e.g., taste or intensity) of the stimuli used (Miller & Holzman, 1981). The nonspecific character of novelty conceivably may have permitted the influence of novel flavor preexposure to endure the acquisition ofCTA.…”
Section: Discussionsupporting
confidence: 74%
“…In Experiments lb and 2b, prior "safe" ingestion of novel saline or saccharin reduced the demonstration of conditioning-enhanced neophobia to casein hydrolysate. Because this effect occurred without apparent diminution of CTA to the novel CS, it appears that prior ingestion history affects neophobia through a process which differs from that by which prior ingestion experience affects CTA (see Braveman &Jarvis, 1978, andMiller &Holzman 1981). …”
Section: Discussionmentioning
confidence: 99%
“…Our results also appear at odds with a growing body of data being interpreted as indicating the "independence" (Braveman & Jarvis, 1978) or "decoupling" (Miller & Holzman, 1981) of flavor neophobia and conditioned taste aversion. These investigators have shown that familiarization procedures that reduce neophobia can leave CT A unaltered.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, had US intensity been less or preexposure duration greater in the Braveman-Jarvis and Miller-Holzman studies, the attenuating effect of preexposure on conditioning and, hence, the contribution of neophobia to CTA would have been evident. In fact, Tarpy and McIntosh (1977) had previously shown that the familiarization procedure used by Braveman and Jarvis (1978) and Miller and Holzman (1981) to reduce neophobia also alters CTA if familiarization is extensive. Thus, it would appear that unlearned fear of novel flavors is, in most cases, simply weaker than conditioned fear and, hence, is altered more easily than CTA by factors that influence fear.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestional neophobia refers to the finding that initial presentation of novel food/drink yields minimal intake relative to that after repeated access (see, e.g., Braveman, 1978;Miller & Holzman, 1981). The unfamiliar appearance of an ingestible may produce neophobia because unfamiliar visual cues may deter approach and, thus, deter the start of ingestion.…”
Section: Roles Of Visual and Taste Cues In Ingestional Neophobia: Resmentioning
confidence: 99%